2017
DOI: 10.1016/j.medici.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of coronary care management and hospital mortality from ST-segment elevation myocardial infarction in the Kazakhstan population: Data from 2012 to 2015

Abstract: The present study demonstrated that hospitalization delay in the treatment of STEMI patients in Kazakhstan population was without significant changes, meanwhile the number of patients perfused within 1h from hospitalization to PCI tended to increase during 2012-2015. The higher hospital mortality was associated with study year, female gender, older age, longer-time from hospitalization to PCI and shorter hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“… 18 The D2D time decreased from 155 minutes to 73 minutes in Kazakhstan over a time period between 2012 and 2015. 19 The D2D time in our center appears to be comparable with the best results reported from developed countries and far shorter than the time in other developing countries. It is worthy of note that most studies have excluded some patients and, as such, have underestimated their reported time.…”
Section: Discussionsupporting
confidence: 86%
“… 18 The D2D time decreased from 155 minutes to 73 minutes in Kazakhstan over a time period between 2012 and 2015. 19 The D2D time in our center appears to be comparable with the best results reported from developed countries and far shorter than the time in other developing countries. It is worthy of note that most studies have excluded some patients and, as such, have underestimated their reported time.…”
Section: Discussionsupporting
confidence: 86%
“…The door-to-door time was reported to be 75 min in a single center [15]. A study from Kazakhstan showed that the door-to-door time decreased from 155 min to 73 min over a time period between 2012 and 2015 [16].…”
Section: Discussionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) and re-infarction are the leading causes of death worldwide 3 . AMI remains the leading fatal disease in Kazakhstan 4 . Therefore, Kazakhstan's national health policy has been predominantly focused on reducing mortality caused by diseases of the cardiovascular system 5 .…”
Section: Introductionmentioning
confidence: 99%